2006
DOI: 10.1270/jsbbs.56.81
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Two Races of Meloidogyne incognita and Resistance Mechanism in Diploid Ipomoea trifida

Abstract: The southern root-knot nematode, Meloidogyne incognita is a noxious and widespread plant-parasitic nematode, that causes serious damage to sweet potato, Ipomoea batatas storage root both in quality and yields (Clark and Moyer 1988). In this crop, therefore, many resistant cultivars have been developed to deal with this destructive pest. One such cultivar, 'Minamiyutaka' was developed using a wild hexaploid accession (K123-11) can be crossed with sweet potato and is highly resistant to nematode (Ono et al. 1977… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…in sweepotato have shown that several genes may be involved in the inheritance to RKN in sweetpotato and that resistance to different RKN species may be conferred by different genes (Cervantes-Flores et al, 2002b;Sano et al, 2002). Histological studies have shown that juvenile (J2 stage) RKN penetrate both susceptible and resistant sweetpotato genotypes as well as other Ipomoea L. species, including I. trifida (Kunth) Don (Komiyama et al, 2006). However, in susceptible genotypes, the nematodes become established, whereas in resistant genotypes, necrotic reactions prevent further pathogen development.…”
mentioning
confidence: 99%
“…in sweepotato have shown that several genes may be involved in the inheritance to RKN in sweetpotato and that resistance to different RKN species may be conferred by different genes (Cervantes-Flores et al, 2002b;Sano et al, 2002). Histological studies have shown that juvenile (J2 stage) RKN penetrate both susceptible and resistant sweetpotato genotypes as well as other Ipomoea L. species, including I. trifida (Kunth) Don (Komiyama et al, 2006). However, in susceptible genotypes, the nematodes become established, whereas in resistant genotypes, necrotic reactions prevent further pathogen development.…”
mentioning
confidence: 99%
“…Interestingly, although Minagawa (1976) previously reported that M. incognita affects the number of tuberous roots in a nematodesusceptible cultivar in Japan, RKNs also seem to affect the number of tuberous roots in highly nematode-resistant cultivars in the roots in which RKNs cannot propagate. In this regard, M. incognita appears to penetrate the root system of both nematode-resistant and susceptible cultivars (Komiyama et al, 2006). RKNs tend to damage roots at an early stage of development, thus inhibiting tuberous root formation, regardless of the resistance of the cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…We can also use resistant cultivars. Southern root-knot nematodes can infect the roots of resistant sweetpotato ( Komiyama et al 2006 , Kondo 1972 ), but this infection tends to induce necrosis that seems to be related to resistance of sweetpotato ( Gentile et al 1962 , Giamalva et al 1963 , Komiyama et al 2006 ). Sasser and Freckman (1987) indicated 31% of nematologists could access nematode-tolerant or nematode-resistant seeds or rootstocks based on worldwide surveys.…”
Section: Southern Root-knot Nematodementioning
confidence: 99%